Deteksi Dini melalui Stimulasi Tumbuh Kembang Anak pada Ibu di Kelurahan Maricaya Selatan - Sitti Mukarramah; Theresia Limbong; Amelia Wong; Jumrah Sudirman (Universitas Mathla'ul Anwar Banten, 2021)
EARLY DETECTION THROUGH STIMULATION OF CHILD DEVELOPMENT IN MOTHERS IN SOUTH MARICAYA VILLAGE. The quality of growth and development of toddlers needs serious attention, getting good nutrition and adequate stimulation. So that children can grow and develop optimally according to their genetic potential and be able to compete in the global era. The purposed of this community service was to increase the knowledge and skills of the mother in providing good and correct stimulation in her child's growth and development. The implementation of this activity was carried out in the South Maricaya Village of the City of Makassar in September - October 2018. There are 3 stages: 1) The stages of preparation included the preparation of an activity plan; 2) The stages of implementing counseling and training stimulation of Child Development; 3) The evaluation stage is posttest knowledge and observing the way the mother stimulates her child. The results obtained were that there was an increase in maternal knowledge of the importance of stimulating child development from 49.89% to 80.04%. The ability of the mother's skills on how to stimulate child development increases from an average value of 4.63 to 9.38 in group I (age of children 0-30 months), and an average value of 5.11 to 11.22 in group II (age of child 31-60 months). The results of growth monitoring are 7 infants / toddlers with 25 underweight / underweight (28%), out of 19 toddlers measured in height, there are 3 (15.8) stunting. Some mothers are less known how to interpret KMS for monitoring the growth of their children. Recommended that the socialization of SDIDTK be improved and the interpretation of KMS in infants/toddlers' mothers be improved. Stimulation of child development if implemented optimally by increasing the ability of health cadres (teenager).